Uma abordagem orientada a modelos para desenvolvimento de aplicações sensíveis ao contexto no ambiente de TV digital - Vale, Igor Magri (2011)
With the definition of the Brazilian System of Digital Television, and the possibility of creating interactive applications, the field of Digital Television (DTV) is an environment to be explored by innovative applications, such as Context-Aware Applications. Context-aware applications use contextual information from the user to trigger services according user s needs or his current situation, and therefore can potentially enrich the user experience when watching TV. The objective of this dissertation is to propose a model-driven methodology to assist the development of these applications in the DTV environment, starting from the modeling phase all the way to the implementation. The target platform is called Ginga, which is the middleware defined by SBTVD in order to support the development of interactive applications. The methodology proposed by this work offers support for (i) modeling the universe of discourse of context-aware applications by means of context models, situation models and (ii) specifying the reactive behaviours of these applications using a rule-based approach. For that, this work proposes a domain-specific language, coined ECA-DL TVD, which allows the specification of reactive behaviours by means of events, conditions and actions. This work also defines a conceptual architecture, which is used to structure the Ginga Component called Context Manager. One of the main contributions of this work lies in the automatic generation of NCL code concerning part of this conceptual architecture, using transformation frameworks and other Model-Driven Development techniques. Finally, two application scenarios are presented in order to demonstrate the viability of such methodology.